Examining Activator and Carbonization Pineapple Crown Leaf Resistor: Wuluh Star Fruit and Calamansi Variant - Intan Kusumawati; Putut Marwoto; Ani Rusilowati; Woro Sumarni; Retno Sri Iswari; Andi Mursidi (Universitas Negeri Semarang, 2022)
Learning in the environmental physics course is directed at sharpening students' sensitivity to overcoming problems and utilizing the potential that exists in the environment. Waste management is the main focus in environmental physics learning, which in this research is pineapple crown leaf waste which has the potential as activated carbon to be processed into resistors. The purpose of this study was to test the activator and carbonization tool for pineapple crown leaves with the highest inhibition value. This activator is in the form of Wuluh star fruit and Calamansi. The carbonization tools are an infrared stove and a blue flame twister furnace. This research method is in the form of an experiment. This activity research is integrated with the STEAM-2C components. The data analysis technique is in the form of comparing the average resistance values ​​of the pineapple leaf resistor variations. It was found that = 0.067 MΩ; = 0.16 MΩ; = 0.12 MΩ; = 0.14 MΩ. It was concluded that the activator and carbonization tool for pineapple crown leaf with the highest inhibition values ​​were the Calamansi activator and Infrared stove carbonization tool. This research is expected to add insight into producing innovations that are tested experimentally as the implementation of environmental physics learning.